Applicability of Unified Theory of Acceptance and Use of Technology Extended to the Consumer Use Context (UTAUT2) in Brazil: An Evaluation of the Model Using a Sample of Internet Users on Smartphones - Faria, Luiz Henrique Lima; Giuliani, Antônio Carlos; Pizzinatto, Nadia Kassouf; Pizzinatto, Andrea Kassouf (Revista de Administração da UFSM, 2014)
This study, using a sample of internet users on smartphones, analyzed through UTAUT2 model in order to test the validity of their constructs in Brazil. We sought to thereby expand the understanding of individual acceptance and use of technology in the context of consumption, evaluating a new model in Brazil. The results of this study revealed the impossibility of using some constructs the original model as predictors of intention and consumption behavior. Future studies that include a larger sample, analysis of other technologies and inclusion of moderating variables were suggested.